THE INFLUENCE OF THE PBL MODEL THROUGH YOUTUBE ON THE LEARNING OUTCOMES OF STUDENTS OF SDN BANYUAJUH 4 - Anifatul Maufirah; Bastia Fatwa Islami; Iskandar Iskandar; Ika Dian Rahmawati (Universitas Negeri Surabaya, 2026)
This study aimed to examine the effect of the Problem-Based Learning (PBL) model through YouTube Education on the learning outcomes of fourth-grade students at SDN Banyuajuh 4. Using a One-Group Pretest–Posttest design with 9 students, the results showed that the average score increased from 36.22 to 88.22, with a significance value of 0.000 (<0.05). It was concluded that PBL through YouTube Education had a significant positive effect on students' learning outcomes. Further studies are recommended using larger samples and control groups.